Three‐Dimensional Anatomy of the Equine Sternum. (9th April 2014) - Eydt, C.; Schröck, C.; Geburek, F.; Rohn, K.; Staszyk, C.; Pfarrer, C.
Summary The sternum is a frequently used anatomical site to obtain bone marrow for diagnostic and therapeutic purposes in equine medicine and surgery. For a safe and reproducible aspiration of sternal bone marrow, a reliable anatomical description of the sternum is mandatory. However, the anatomical literature provides very heterogeneous information concerning the structure and number of sternebrae. Isolated sterna (horses of different ages) underwent clinical computed tomography, and single sternebrae were scanned by microcomputed tomography. Data sets were analysed in detail, the dimensions of each sternebra were determined, and correlations to the age and weight were generated. A uniform arrangement of seven sternebrae within the equine sternum was obtained, whereas the 6th and 7th sternebrae were fused in all sterna. The cranial sternebrae (sternebrae 1–3) had a lentiform shape with flattened lateral sides, while the caudal sternebrae (6 and 7) were flattened dorso‐ventrally. In contrast, sternebrae 4 and 5 were spherical. The single sternebrae were well demarcated to the chondral sternum and showed two different zones. The periphery consisted of radiodense woven tissue, while in the centre the radiodense tissue was loosely arranged and contained large cavities with radiolucent tissue. A thin lamina (substantia corticalis) of <1 mm was arranged around the peripheral zone. There was no correlation between the body weight and the dimensions of the sternebrae, but there was a positive correlation to the age of the horses. The obtained data provide a sufficient basis to establish a standard nomenclature of the equine sternum.